General Provisions for Committees Emanating from The Bank's Board of Directors (Al-Mukhtar Journal of Legal Science, 2025)
Given the complexity of banks' activities and the scale of their relationships and transactions, this has placed additional challenges on bank boards of directors. The banking governance codes, followed by many legislators and central banks, recommend the creation of several specialized committees in specific areas, such as auditing, risk management, remuneration assessment, and governance, attached to the Board of Directors. These committees are tasked with organizing and facilitating the work of these boards, improving their efficiency, transparency, and compliance with governance principles.
Keywords: Bank Governance; Board Committees; Governance Guide; Basel Committee